Pengaruh Strategi Bisnis, Biaya Transfer, Dan Intensitas Modal Terhadap Penghindaran Pajak Yang Dimoderasi Tanggung Jawab Sosial - Yosi Ika Putri; Nera Marinda Machdar (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Companies often carry out this tax avoidance strategy in an effort to reduce the amount of tax they have to pay. There are two ways for businesses to lower the taxes they pay. In the first case, the business world can reduce the tax value by implementing tax avoidance while still complying with relevant tax laws. The second alternative is for business actors to reduce the tax value by carrying out tax avoidance activities that violate tax regulations. This research examines the relationship between business strategy, transfer pricing, and capital intenssity on tax avoidance moderated by corporate social responsbility. This research uses a qualitative descriptive research methodology. The data collection method in this research is literature study. The research results show that business strategy, transfer costs, and capital intent have an influence on tax avoidance. As well as business strategy, transfer costs and capital intentions can be mediated by CSR on tax avoidance.